Music and Your Mind : Listening with a New Consciousness. - Kenny, Carolyn (Barcelona Publishers, 2014)
A ground-breaking book that presents integrated ways of listening to music, exploring the imagination, and traveling through expanded states of consciousness. Individual and group exercises are provided. This book laid the foundation for the formulation of Bonny's method, Guided Imagery and Music, an indepth form of psychotherapy and healing.